PESAN DAKWAH DALAM IKLAN HILO SOLEHA DI CHANNEL YOUTUBE HILO SOLEHA (Analisis Semiotika Rolland Barthes) - Elfia Damayanti; Kayyis Fithri Ajhuri (JUSMA: Jurnal Studi Islam dan Masyarakat, 2023)
The message of da'wah is worthy of research because of the fading problem of faith and today's lifestyle mixed with western culture. With the fact that there are fewer advertisements that contain elements of da'wah messages, the authors are interested in examining the da'wah messages contained in the Hilo Soleha advertisement. The purpose of this study was to determine the denotative, connotative, mythical and representational meanings of da'wah messages in Hilo Soleha advertisements. This study uses qualitative methods to describe and explain Hilo Soleha advertisements on Hilo Soleha's youtube channel. The data collection techniques used are observation and documentation, then analyzed using the Rolland Barthes semiotics method to get a deeper understanding and tested its validity using the observation persistence technique. The results of the analysis of this study indicate that 1) The meaning of denotation in Hilo Soleha's advertisement is someone who lives life with an optimistic spirit, carrying out His God's commands 2) The meaning of the connotation is that as a human being, we should carry out religious orders such as always wearing the hijab, and doing good deeds 3) The meaning of the myth is that a Muslim woman wherever her place is required to be a creative, cheerful person and spread a smile of kindness with a positive aura 4) The representation of her da'wah message is a Muslim woman who maintains her chastity and covers her genitals, mu'amalah ma'al ghair to fellow co-workers, has good morals and obeys God's commandments, respect others, be gentle and humble in heart.